2014
DOI: 10.1111/gbi.12123
|View full text |Cite
|
Sign up to set email alerts
|

Mineralization of Alvinella polychaete tubes at hydrothermal vents

Abstract: Alvinellid polychaete worms form multilayered organic tubes in the hottest and most rapidly growing areas of deep-sea hydrothermal vent chimneys. Over short periods of time, these tubes can become entirely mineralized within this environment. Documenting the nature of this process in terms of the stages of mineralization, as well as the mineral textures and end products that result, is essential for our understanding of the fossilization of polychaetes at hydrothermal vents. Here, we report in detail the full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(41 citation statements)
references
References 73 publications
9
32
0
Order By: Relevance
“…It has been demonstrated that near hydrothermal vents, tubeworms can remarkably influence metal distribution, and that sulfide minerals (especially iron sulfides) accumulate on surfaces or are entombed within the tube interlayers during tube-building episodes (Maginn et al, 2002; Peng et al, 2009). With the process of mineralization, certain tubes are gradually replaced by pyrite and marcasite and become completely fossilized (e.g., tube T3-1, Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that near hydrothermal vents, tubeworms can remarkably influence metal distribution, and that sulfide minerals (especially iron sulfides) accumulate on surfaces or are entombed within the tube interlayers during tube-building episodes (Maginn et al, 2002; Peng et al, 2009). With the process of mineralization, certain tubes are gradually replaced by pyrite and marcasite and become completely fossilized (e.g., tube T3-1, Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Haas et al in 2009, for instance, observed that the organic tubes were replaced by aragonite after the death of the worms, possibly due to the mineralization of bacterial communities colonizing the tube. External and internal colonization of siboglinid tubes has previously been described (López-García, Gaill & Moreira, 2002;Duperron et al, 2009;Petersen et al, 2012) with high abundance of Epsilonproteobacteria (López-García, Gaill & Moreira, 2002;Georgieva et al, 2015). SEM and TEM micrographs showed highly colonized tubes in Al Gacel MV specimens (Fig.…”
Section: The Tube As a New Nichesupporting
confidence: 51%
“…Tube fossils of siboglinid worms from vent sites are dated from the Silurian period, ca. 430 Ma ago (Little et al, 1998;Hilário et al, 2011;Georgieva et al, 2015). Taxonomic groups of the Siboglinidae family are described as a fundamental part of the core chemosynthetic community in reduced environments (Hilário et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, the dwelling tubes that many annelids create are often more robust structures that have a greater likelihood of becoming preserved as fossils (Ippolitov et al 2014;Georgieva et al 2015a), and especially so within vents and seeps where rapid mineral precipitation often favours fossilization.…”
Section: Introductionmentioning
confidence: 99%
“…The few existing studies show that vestimentiferan and alvinellid tubes at hydrothermal vents are preserved primarily by iron sulphides, with details of outer tube ornament and fibrous textures sometimes very intricately replicated (Cook & Stakes 1995;Georgieva et al 2015a). At seeps, aragonite can preserve the original finely multilayered structure of the tube walls of the vestimentiferan Escarpia southwardae, also retaining details of fraying of the fibrous tube wall and the delamination (layer separation) of tube walls (Haas et al 2009).…”
Section: Introductionmentioning
confidence: 99%